Analyzing Science Test Items and Higher Order Thinking Skills of Fifth Graders - Mardi . (BIOEDUKASI, 2018)
Indonesian students got low achievement in many international studies of evaluation, such as in Trend in International Mathematics and Science Study (TIMSS). It is because they unfamiliar with higher order thinking skill questions. Generally, assessment in Indonesia contains less of higher order thinking questions and do not fit with the international standard of evaluation. The purposes of this study were to identify the test items of Test of Standarisasi Hasil Belajar (SHB) and to examine the capability of students of fifth grade to answer higher order thinking skills (HOTS) questions. The method uses was mix method (qualitative and quantitative). Test Standarisasi Hasil Belajar (SHB) Year 2017/2018 of Banyuwangi Regency for fifth grade was used. Twenty-seven fifth graders were participated in paper test. The result showed that the test contains of cognitive domain of knowing, applying, and reasoning of 48.9%, 40% and 11.1%, respectively. The test of capability of students to answer HOTS questions revealed low achievement of 80% and high achievement of 5%. In summary, the reasoning domain of the test should be more developed to encourage students’ capability in answering HOTS questions. Keywords: science test items, TIMSS, HOTS, fifth grade.